Comparison of different methods to measure contact angles of soil colloids - Shang, Jianying; Flury, Markus; Harsh, James B.; Zollars, Richard L. (Journal of colloid and interface science, 2008)
We compared five different methods, static sessile drop, dynamic sessile drop, Wilhelmy plate, thin-layer wicking, and column wicking, to determine the contact angle of colloids typical for soils and sediments. The colloids (smectite, kaolinite, illite, goethite, hematite) were chosen to represent 1:1 and 2:1 layered aluminosilicate clays and sesquioxides, and were either obtained in pure form or synthesized in our laboratory. Colloids were deposited as thin films on glass slides, and then used for contact angle measurements using three different test liquids (water, formamide, diiodomethane). The colloidal films could be categorized into three types: (1) films without pores and with polar–liquid interactions (smectite), (2) films with pores and with polar–liquid interactions (kaolinite, illite, goethite), and (3) films without pores and no polar–liquid interactions (hematite). The static and dynamic sessile drop methods yielded the most consistent contact angles. For porous films, the contact angles decreased with time, and we consider the initial contact angle to be the most accurate. The differences in contact angles among the different methods were large and varied considerably: the most consistent contact angles were obtained for kaolinite with water, and illite with diiodomethane (contact angles were within 3°); but mostly the differences ranged from 10° to 40° among the different methods. The thin-layer and column wicking methods were the least consistent methods.